ASPECTS OF ECONOMIC, CULTURAL, AND SOCIAL ROLES RELATED TO EARLY MARRIAGE IN SERDANG VILLAGE, SOUTH BANGKA - Amalia Addini; Fenny Etrawati; Ikhwanul Nurimansyah (LLDIKTI Wilayah X, 2023)
Bangka Belitung Province ranks first among 34 provinces with a percentage 18.76%. Serdang Village is a village in Toboali District, South Bangka Regency with a high percentage of early marriage, which is 29%. This study aims to examine more deeply about the economic, cultural, and resource aspects and social support related to adolescent decisions to get married at an early age in Serdang Village. This study uses a qualitative and sample approach selected by purposive sampling by involving 22 informants. Key informant consists of 8 teenagers of early marriage perpetrators and 8 parents or teenage relatives. While the expert key informant is the Head of DKPPKB, Head of Population Control, Customary Leaders, Religious Leaders, Community Leaders, and Youth Leaders. Researchers use triangulation techniques to obtain data validity. The results of this study show that the majority of teenagers want to get married factor is the limited cost of daily needs and education, as well as the divorce of parents which has impact on the economic resilience of children. In addition, the existence of a culture of mass marriage also attracts the incidence of early marriage and the lack of the role of parents and relatives in preventing early marriage.